MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV MENGGUNAKAN APLIKASI GOOGLE CLASSROOM PADA PEMBELAJARAN DARING - ISTIQOMAH ISTIQOMAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This study aims to determine the improvement of student learning outcomes in class IVA MI Miftahul Jannah Cijantung by utilizing the Google Classroom application in online learning as a learning strategy during the Covid-19 pandemic on the circular shape material. This research is a classroom action research which was carried out for two cycles. Each cycle consists of stages of planning (planning), action (action), observation (observation), and reflection (reflection). The learning strategy used is by utilizing the Google Classroom application. The advantage of this application is that it can make it easier for teachers to manage learning and convey information precisely and accurately to students. The results of this study indicate that learning strategies by utilizing technology in the form of the Google Classroom application for online learning during the Covid-19 pandemic can improve student learning outcomes for the material around flat shapes for class IVA MI Miftahul Jannah Cijantung for the 2020-2021 academic year as evidenced by test results at the end of the cycle. First, there were 19 students with a percentage of completeness of 59.4% and an increase in the percentage of completeness in the second cycle of 78.13% from 32 students. This shows that the target percentage of students' completeness has exceeded the minimum limit value. ABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatkan hasil belajar siswa kelas IVA MI Miftahul Jannah Cijantung dengan memanfaatkan aplikasi google classroom pada pembelajaran daring sebagai salah satu strategi pembelajaran selama pandemi Covid-19 pada materi keliling bangun datar. Penelitian ini adalah penelitian tindakan kelas yang dilaksanakan selama dua siklus. Setiap siklus terdiri atas tahap perencanaan (planning), tindakan (action), pengamatan (observation), dan refleksi (reflection). Strategi pembelajaran yang digunakan dengan memanfaatkan aplikasi google classroom. Kelebihan dari aplikasi ini adalah dapat mempermudah guru dalam mengelola pembelajaran dan menyampaikan informasi secara tepat dan akurat kepada peserta didik. Hasil dari penelitan ini menunjukkan bahwa strategi pembelajaran dengan memanfaatkan teknologi berupa aplikasi google classroom pada pembelajaran daring selama pandemi Covid-19 dapat meningkatkan hasil belajar siswa materi keliling bangun datar kelas IVA MI Miftahul Jannah Cijantung Tahun pelajaran 2020-2021 dibuktikan dengan hasil tes pada akhir siklus I terdapat 19 peserta didik dengan persentase ketuntasan sebesar 59,4% dan mengalami peningkatan persentase ketuntasan pada siklus II sebesar 78,13% dari 32 peserta didik. Hal ini menunjukkan bahwa target persentase ketuntasan peserta didik telah melebihi dari nilai batas minimal.